Examining quality, perceived value and satisfaction of Penang delicacies in predicting tourists’ revisit intention / Atikahambar Yusni - Yusni, Atikahambar (2012)
Penang commonly referred to as the Pearl of the Orient, is one of Asia’s famous islands. Besides that it is an international tourist destination famous for its many attractions which are steeped in history as well as for its scenic beauty with white sandy beaches, beautiful landscape and its unique and diverse cultures and food. In line with the tourism bodies or states government effort in promoting ‘The Visit Penang Year 2010 to 2012’ a well diverse blend of programs and activities were conducted and one of it is Penang Food Fair. As mentioned above there have are variety of different food to enjoy every day at Penang sites. Penang’s cultural diversity is reflected par excellence in its cuisine which is a mixture of Malay, Chinese, Indian, Siamese and European. Due to that, Penang is highlighted as the one of states for gastronomy routes to Malaysia. Relates to above statements, this state is well known for food lovers, which is full of local delicacy and cuisine which tourists’ come to Penang to taste the island’s unique cuisine. As a result, this has made Penang to be given the title of food capital of Malaysia. The study focuses on examining quality, perceived value and satisfaction of Penang delicacies in predicting tourists’ revisit intention. The study utilized the self-administered questionnaire technique which international tourist’s who visited or having their vacation trips in the city of Penang from the various parts of the world was a respondents. Data was successfully gathered from a sample of three hundred twenty eight (328) respondents, yielding almost 82% response rate. The data were analyzed using inferential statistics such as, reliability test and multiple regressions to confirm proposed hypothesis, simultaneously answering the posited research questions. In order to test the significant of the study, the mediation test on tourists’ satisfaction mediates the relationships between quality, perceived value and revisit intention was conducted. The findings of this study revealed that tourists’ satisfaction have positive relationship between quality, perceived value, and tourists’ satisfaction. It is therefore suffice to say that the findings of this study enables greater comprehension on examining quality, perceived value and satisfaction of Penang delicacies in predicting tourists’ revisit intention and give positive impact on tourism industry in order for targeting international tourists’ arrival in Penang.